Wild Triatoma infestans, a potential threat that needs to be monitored - François Noireau (Memórias do Instituto Oswaldo Cruz., 2009)
The current persistence of Triatoma infestans, and therefore of Chagas disease transmission, in the Andean valleys of Bolivia and the Gran Chaco (precisely where wild populations of the vector are widespread), indicates a possible relationship between these two occurrences. This paper provides an overview of the current knowledge regarding wild T. infestans in Bolivia. The different morphs of the wild vector, their known distributions and some traits of their biology and ecology are presented. Particularly interesting is the considerable behavioural and chromatic plasticity that is displayed by wild T. infestans. According to the biogeographic region, different morphs of the vector occur in rupicolous habitats (common form and Mataral morph in Andean wild T. infestans) or arboreal ones ("dark morph" populations from the Chaco). The high genetic variability found at the microgeographical scale in Andean wild T. infestans favours the hypothesis that the Andes were the centre of origin and dispersal of T. infestans throughout South America. The relevant question regarding the origin of domestic populations is also addressed. Finally, current considerations of the epidemiological significance of wild T. infestans are discussed in the context of recent discoveries. Even if several observations support the epidemiological risk represented by wild T. infestans, the climatic and environmental conditions of their distribution areas would not favour the continued flow of triatomines between sylvatic refuges and domestic environments.